Efficiency of stable liquide chlorine dioxide (ClO₂) in sanitation of water distribution system in poultry production-synthesis of theoretical and experimental findings (VETERINARIA, 2025)
Modern veterinary practice faces growing challenges in the field ofbiosecurity, especially in intensive livestock and poultry production.One of the most underestimated, yet critical, factors in maintainingthe health status of animals is the quality of drinking water andthe hygienic safety of the water distribution system. Although ineveryday veterinary practice, the leading causes of health disordersare often attributed to diet, environmental factors, or genetic potential,numerous cases indicate that water is a key vector of microbialcontamination, primarily through biofilm structures that form ininternal water distribution systems. Due to the increasing incidence ofresistant bacterial strains and the limited effectiveness of conventionaldisinfectants, such as chlorine, there is a growing need for new, safer,and more effective sanitation methods.Stabilised liquid chlorine dioxide (ClO₂) is emerging as a potentalternative to conventional agents. This paper represents a synthesisof experimental and review findings related to the use of stabilisedliquid chlorine dioxide for the rehabilitation of the drinking systemin laying hens suffering from colisepticemia. Through a case studyof a farm with a recorded problem of systemic infection caused byEscherichia coli, the causes of contamination, remediation measures,as well as the effects achieved in terms of biofilm reduction, mortalityand microbiological load of water were analyzed. Along with the casereport, the paper analyzes and expands the context of the effectivenessof stabilised liquid chlorine dioxide, based on the literature andprevious studies. Stabilised ClO₂, in contrast to its gaseous form,offers safer handling, a prolonged residual protection effect, andminimal toxicity.The paper emphasises the importance of microbiological control andimproved sanitation of water supply systems in poultry production,and highlights stabilised liquid chlorine dioxide as a highly effectivetool in the fight against biofilm and resistant bacterial strains.
Keywords: Animal production; disinfection; prevention; stable liquid chlorine dioxide